Removal of Methylene Blue by Agricultural Waste of Cicer arietinum - Kale, A.A.; Deshmukh, M.R.; Deshpande, N.R.; Kashalkar, R.V. (Asian Journal of Chemistry, 2010)
Two kinds of adsorbents were prepared from the agricultural waste of Cicer arietinum. Both adsorbents have good uptake capacity of methylene blue dye. It was observed that removal of dyes is dependent on concentration of the dye, time and amount adsorbent of material used.